A study on palm fiber reinforces as a filament in portable FDM - Marwah @ Omar, Omar Mohd Faizan; Mohamad, Elmy Johana; Hj Ibrahim, Mustaffa (Asian Research Publishing Network (ARPN)., 2016)
The growth of renewable energy has been identified globally to ensure minimal environmental harm. Due to this situation, the development of green technology has enhanced the growth of renewable energy in the country. One of lignocellulosic biomass feedstock, oil palm frond was the raw material for a potential second-generation bioethanol production. Meanwhile, the sample characterizations were conducted by using the melt flow index. In addition, the 10% of oil palm fronds (OPF) was used and mixed with the HDPE which produce the composite grains. The main goals of the present work are the evaluation of the influence of several variables and test parameters on the melt flow index (MFI) of thermoplastics, and the determination of the uncertainty associated with the measurements. Hence, the capillary flow of a high-density polyethylene (HDPE) melts was studied. The shearing flow of polymeric fluids is encountered in a number of polymer processing operations. In other words, viscosity under simple shear is an important material parameter used for determining the pumping efficiency of an extruder, the pressure drop through a die, designing balanced flow runner systems in multiple cavity injection molding, computing the temperature rise due to viscous heat generation during processing. In this works, Thermagravimetric Analysis (TGA) is one of the branches under the thermal analysis, which is to determine the decomposition of the raw material that has been heat in certain temperature according the standard temperature of specific materials. Most of the thermal analysis, testing uses the weight of the sample within milligram or gram. Next, the process in the sample under DTA study is manifested by deviation of temperature difference from its background. This difference ΔT is not directly proportional to the rate of the process (dα/dt) but includes also the effect of heat inertia proportional to the slope dΔT/dt as it was derived. The filaments are inferior to the fibers for cement–matrix composites, but are superior to the fibers for polymer–matrix composites.